1987
DOI: 10.1159/000206000
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Methylprednisolone Pulse Therapy in Childhood Chronic Thrombocytopenia

Abstract: Nineteen children with chronic idiopathie thrombocytopenia (ITP) were treated with a single intravenous injection of methylprednisolone (MP), 15 mg/kg/day, for 3 consecutive days. The 3-day pulses gave rise to a positive and fast therapeutic response with increase of the platelet count in about three quarters of the patients. The platelet count remained above 50 × 109/1 for more than 1 month in 10 children. Eight out of them still presented a safe platelet count ( > 50 × 109/1) 4 months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Forty-nine children with acute ITP were divided into three groups consisting of 17, 16 and 16 children, respec- (table 2). Although, in our protocol, intravenous methylprednisolone was used for longer periods and in higher doses than by Del Principe et al [8], all the above findings are evidence for the efficacy of HIVMP treatment in childhood ITP. I would like to add that with the exception of Cushingoid appear ance, side effects of corticosteroid treatment, such as hypertension, hyperglycemia, glucosuria, corneal opacities, have not been observed.…”
mentioning
confidence: 49%
“…Forty-nine children with acute ITP were divided into three groups consisting of 17, 16 and 16 children, respec- (table 2). Although, in our protocol, intravenous methylprednisolone was used for longer periods and in higher doses than by Del Principe et al [8], all the above findings are evidence for the efficacy of HIVMP treatment in childhood ITP. I would like to add that with the exception of Cushingoid appear ance, side effects of corticosteroid treatment, such as hypertension, hyperglycemia, glucosuria, corneal opacities, have not been observed.…”
mentioning
confidence: 49%
“…Our results with oral prednisone coincide with Lusher & Iyer's (9) conclusion, based on a retrospective analysis of 236 children with ITP, although this is contrary to several more recent studies (10)(11)(12). Platelet response in 3 d was observed only in the HIVMP groupas it was in chronic ITP (6,13). This early platelet response was also observed in most of the 6 patients unresponsive to oral prednisone who were treated 4 months later with HIVMP (Table 2).…”
Section: Discussionmentioning
confidence: 75%
“…The authors do not specify, in fact, if the nonresponders had been splenectomized. As a matter of fact, we treated unsplenectomized children [1], so that our patients were not comparable with those reported by Lam and Yuen. Moreover, it is unknown if the patient who de veloped a severe thrombocytopenia had been treated before with long-term steroid therapy and when it was stopped.…”
Section: Replymentioning
confidence: 71%
“…The report on methylprednisolone (MP) pulse therapy in childhood chronic idiopathic thrombocyto penic purpura (ITP) by del Principe et al [1] indicated it to be safe and promising. Our result in 3 children with chronic ITP treated with this drug, however, was discouraging.…”
Section: Méthylprednisolone In Childhood Idiopathic Thrombocytopenic mentioning
confidence: 99%